The C-terminal domain of Clostridium perfringens alpha toxin as a vaccine candidate against bovine necrohemorrhagic enteritis. (December 2016) - Goossens, Evy; Verherstraeten, Stefanie; Valgaeren, Bonnie; Pardon, Bart; Timbermont, Leen; Schauvliege, Stijn; Rodrigo-Mocholí, Diego; Haesebrouck, Freddy; Ducatelle, Richard; Deprez, Piet; Van Immerseel, Filip
Abstract Bovine necrohemorrhagic enteritis is caused byClostridium perfringens and leads to sudden death. Alpha toxin, together with perfringolysin O, has been identified as the principal toxin involved in the pathogenesis. We assessed the potential of alpha toxin as a vaccine antigen. Using an intestinal loop model in calves, we investigated the protection afforded by antisera raised against native alpha toxin or its non-toxic C-terminal fragment againstC. perfringens -induced intestinal necrosis. Immunization of calves with either of the vaccine preparations induced a strong antibody response. The resulting antisera were able to neutralize the alpha toxin activity and theC. perfringens -induced endothelial cytotoxicity in vitro. The antisera raised against the native toxin had a stronger neutralizing activity than those against the C-terminal fragment. However, antibodies against alpha toxin alone were not sufficient to completely neutralize theC. perfringens -induced necrosis in the intestinal loop model. The development of a multivalent vaccine combining the C-terminal fragment of alpha toxin with otherC. perfringens virulence factors might be necessary for complete protection against bovine necrohemorrhagic enteritis.